Consumer preferences for wool production attributes - Chen, Yun-Ju (Kelly) (Kansas State University, 2008)
The U.S. wool demand has declined since 1950s due to the increasing demand for synthetic fibers. This research aims to study U.S. consumers' preferences for wool attributes to help the wool industry developing marketing strategies targeting certain groups of consumers. This research can be divided into two parts: 1) examining consumers' willingness-to-pay for wool attributes including country-of-origin, organic, animal-friendly, environment-friendly, and 2) investigating whether or not the consumer segments can be identified from consumers' demographic and psychographic characteristics on product purchasing behavior with respect to the wool attributes. In order to achieve the purpose of this research, the choice experiment was applied to examine consumers' preferences for wool attributes. Both mail and on-line surveys were conducted. The mail survey included three versions: basic version, version with definitions of attributes, and version with both definitions and information about wool attributes, with ## responses received (a 29 percent response rate). The on-line survey contained the basic version and the version with both definitions and information about wool attributes, with 514 responses received. Conditional logit and multinomial logit models were used to examine willingness-to-pay for wool attributes and consumer segments, respectively. Results indicated that a certain portion of U.S. consumers preferred wool over acrylic products. Findings also suggested that it is likely beneficial for wool producers to differentiate their products by promoting products' attributes, such as organic, animal-friendly, and environment-friendly. Further, brief information on product attributes provided with labels could increase consumers' WTPs. Results here revealed that to increase wool producers' revenues effectively, it is necessary to advertise their value-added wool products to different consumer segments.
Keywords: willingness-to-pay; wool; animal-friendly; organic; environment-friendly; Economics, Agricultural (0503)